2011
DOI: 10.1002/eji.201141746
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced IL‐10 production by CD4+ T cells primed in IL‐15Rα‐deficient mice

Abstract: In this study, we investigated the functional outcomes of CD4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…However, this study did not investigate the status of epithelial cell damage, subsequent regeneration, and the role of IL-22. It is also important to note that the lack of IL-15Rα has been implicated in enhanced production of IL-10 44 . Thus, an overall reduction in the mortality could be attributed to a reduced recruitment of T cells that results in significantly less inflammation and pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…However, this study did not investigate the status of epithelial cell damage, subsequent regeneration, and the role of IL-22. It is also important to note that the lack of IL-15Rα has been implicated in enhanced production of IL-10 44 . Thus, an overall reduction in the mortality could be attributed to a reduced recruitment of T cells that results in significantly less inflammation and pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…BM-DCs were cultured and prepared as previously described. [69][70] Briefly, total BM cells were collected from the femurs and tibias of BALB/c mice and depleted of red blood cells with ACK lysis buffer (0.15 M NH 4 Cl, 1 mM KHCO 3 , 0.1 mM EDTA, pH 7.2). Cells were then cultured in complete RPMI-1640 medium supplemented with 20 ng/mL CSF2 (Peprotech, 315-03), 10% fetal bovine serum, 50 mM 2-ME (Gibco TM , 21985023), 100 unit/mL penicillin, and 100 mg/mL streptomycin (Gibco TM , 15140122) in a humidified 5% CO 2 incubator at 37 C. On d 3, 30 mL fresh media with 20 ng/mL CSF2 was added.…”
Section: Bm-dc Preparationmentioning
confidence: 99%
“…19,35 Our results ( Figure 5) confirm the observation that the absence of IL-15 does not alter the frequency of Tregs. 36 On the other hand, BDC2.5 TCR Tg CD4 1 T cells that had expanded in the absence of IL-15 showed reduced antigeninduced differentiation into IFN-c producing cells (Figure 7). Despite the reduction in IFN-c production, the ability of BDC2.5 cells to induce T1D in NOD.scid.Il15 2/2 recipients 21 suggests that increase in the frequency of autoantigen specific T cells, as observed with TCR Tg mice, may overcome the critical threshold of islet-antigen specific T cells required to cause pathology.…”
Section: Discussionmentioning
confidence: 96%
“…For instance, it has been shown that lack of IL-15 skewed the antigen specific CD4 1 T cells to produce IL-10 or IL-17. 36,37 Accordingly, autoimmune diseases mediated by Th17 cells such as experimental autoimmune encephalomyelitis are aggravated by the absence of IL-15. 36,37 In this study, we have identified a novel role for IL-15 in restraining the homeostatic expansion of CD4 1 T cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation